Supplement of corn silk / Muhammad Amir Asyraaf Azman, Muhammad Ajwad Saidina Umor and Syazani Adham Salli Adi - Azman, Muhammad Amir Asyraaf; Saidina Umor, Muhammad Ajwad; Salli Adi, Syazani Adham (Faculty of Plantation and Agrotechnology, 2023)
A corn hair is a bunch of bud heads that come from the female flower corn plants, shaped like threads and yellowish hairs. The function of corn hair is to trap pollen during pollination. Corn hair has bioactive compounds that can act as antioxidants when consumed. The benefits can be obtained through processed corn hair products, corn silk capsules are a food supplement and not a means to treat, prevent, or cure disease. Corn silk, the long, silky, yellowish threads found within corn ear husks, is the major component of the capsules.